The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Divergent water use efficiency trends among eastern North American temperate tree species - Jacob D. Malcomb; Howard E. Epstein; Matthew A. Vadeboncoeur; Daniel L. Druckenbrod; Matthew Lanning; Lixin Wang; Heidi Asbjornsen; Todd M. Scanlon (Oecologia, 2025)
Both theory and observations suggest that tree intrinsic water use efficiency (iWUE)—the ratio of photosynthetic carbon assimilation to stomatal conductance to water—increases with atmospheric CO 2 . However, the strength of this relationship varies across sites and species, prompting questions about additional physiological constraints and environmental controls on iWUE. In this study, we analyzed tree core carbon isotope ratios to examine trends in, and drivers of, iWUE in 12 tree species common to the temperate forests of eastern North America, where forests have experienced changes in CO 2 , climate, and atmospheric pollution in recent decades. Across all site-species combinations, we found that tree iWUE increased 22.3% between 1950 and 2011, coinciding with a 25.2% increase in atmospheric CO 2 . iWUE trajectories varied markedly among tree functional groups and within species across sites. Needleleaf evergreen iWUE increased until circa 2002 before declining in recent years, while iWUE of broadleaf deciduous species continued to increase. The analysis of environmental controls on iWUE trends revealed smaller increases in iWUE in trees subjected to higher atmospheric pollution loads. Our results suggest that tree functional characteristics and atmospheric pollution history influence tree response to atmospheric CO 2 , with implications for forest carbon and water balance in temperate regions.

Proteoglycan-4 (PRG4) serum concentration is lower in aged mice, and genetic deficiency impacts survival probability, blood parameters, and bone during aging - Adam P. Tanguay; Nikhil G. Menon; Emma Slavin; Mikayla Moody; Erin McEwen; Gregory D. Jay; Joseph Lorenzo; Jenna M. Bartley; Vanessa M. Scanlon; Alix C. Deymier; Tannin A. Schmidt (GeroScience, 2025)

Automated device for rapid sample cooling via controlled submersion - Purva Joshi; Zachary Chau; Shaun Keating; Colby Langer; Grace Matheson; Emily Devorsetz; Natalie Scanlon; Mehmet Toner; Rebecca D. Sandlin (Cryobiology, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

GEMAS: Chemical weathering of silicate parent materials revealed by agricultural soil of Europe - Philippe Négrel; Anna Ladenberger; Clemens Reimann; Alecos Demetriades; Manfred Birke; Martiya Sadeghi; S. Albanese; M. Andersson; R. Baritz; M.J. Batista; A. Bel-lan; D. Cicchella; et al. (Chemical Geology, 2023)

Distribution of rare earth and other critical elements in lignites from the Eocene Jackson Group, Texas - James C. Hower; Peter D. Warwick; Bridget R. Scanlon; Robert C. Reedy; Tristan M. Childress (International Journal of Coal Geology, 2023)

Sixty years of global progress in managed aquifer recharge - P. Dillon; P. Stuyfzand; T. Grischek; M. Lluria; R. D. G. Pyne; R. C. Jain; J. Bear; J. Schwarz; W. Wang; E. Fernandez; C. Stefan; M. Pettenati; et al. (Hydrogeology Journal, 2019)

Climate seasonality as an essential predictor of global fire activity - Michael V. Saha; Todd M. Scanlon; Paolo D'Odorico (Global Ecology and Biogeography, 2019)
Aim Fire is a globally important disturbance that affects nearly all vegetated biomes. Previous regional studies have suggested that the predictable seasonal pattern of a climatic time series, or seasonality, might aid in the prediction of average fire activity, but it is not known whether these findings are applicable globally. Here, we investigate how seasonality can be used to explain variations in fire activity on a global scale. Location Global, 60° S–60° N. Time period Data averaged over the period 1999–2015. Methods We describe a method to partition a periodic seasonal cycle into two seasons and define conceptually simple temporal metrics that describe spatial variability in seasonality. We explore the usefulness of these metrics in explaining global fire activity using the average monthly time series of precipitation and temperature and a flexible machine learning procedure (random forests). Results A simple model that uses only precipitation and temperature amplitude and synchrony between wet and warm seasons correctly predicts 66% of the variability in global fire activity, substantially more than a model with mean annual temperature and precipitation. A more complex model that includes all nine metrics predicts 87% of variability in global fire activity. Main conclusions This study shows that seasonality of temperature and precipitation can be used to predict multi‐year average fire activity in a globally relevant way. The mechanisms highlighted in our work could be used to improve global fire models and enhance their ability to represent the spatial patterns of fire activity. Our method might also be useful in hindcasting historical fire using reanalysis or predicting future fire regimes using coarse output from climate models.

What caused the spring intensification and winter demise of the 2011 drought over Texas? - D. Nelun Fernando; Kingtse C. Mo; Rong Fu; Bing Pu; Adam Bowerman; Bridget R. Scanlon; Ruben S. Solis; Lei Yin; Robert E. Mace; John R. Mioduszewski; Tong Ren; Kai Zhang (Climate Dynamics, 2016)

Non-normal distribution of the top-of-atmosphere satellite optical measurements over calibration sites - Javier Gorroño; Agnieszka Bialek; Paul D. Green; Peter Harris; Tracy Scanlon; Nigel P. Fox; Craig Underwood (International Journal of Remote Sensing, 2016)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Chemical Synthesis of a Fluorescent IGF-II Analogue - Jade M. Cottam; Denis B. Scanlon; John A. Karas; Antonio N. Calabrese; Tara L. Pukala; Briony E. Forbes; John C. Wallace; Andrew D. Abell (International Journal of Peptide Research and Therapeutics, 2013)

Mass Spectral Identification of Vc1.1 and Differential Distribution of Conopeptides in the Venom Duct of Conus victoriae. Effect of Post-Translational Modifications and Disulfide Isomerisation on Bioactivity - A. Townsend; B. G. Livett; J.-P. Bingham; H.-T. Truong; J. A. Karas; P. O’Donnell; N. A. Williamson; A. W. Purcell; D. Scanlon (International Journal of Peptide Research and Therapeutics, 2009)

Factors affecting river health and its assessment over broad geographic ranges: The Western Australian experience - S. A. Halse; M. D. Scanlon; J. S. Cocking; M. J. Smith; W. R. Kay (Environmental Monitoring and Assessment, 2007)

Influence of surface heterogeneity on scalar dissimilarity in the roughness sublayer - Christopher A. Williams; Todd M. Scanlon; John D. Albertson (Boundary-Layer Meteorology, 2007)

Genetic variation at the growth hormone (GH1) and growth hormone receptor (GHR) loci as a risk factor for hypertension and stroke - Martin Horan; Vicky Newsway; Yasmin; Mark D. Lewis; Tammy E. Easter; D. Aled Rees; Arti Mahto; David S. Millar; Annie M. Procter; Maurice F. Scanlon; Ian B. Wilkinson; Ian P. Hall; et al. (Human Genetics, 2006)

Application of a quartz crystal microbalance to evaluate biodegradability of starch by Bacillus subtilis - M. Jenkins; M. Horsfall; D. Mathew; M. Scanlon; R. Jayasekara; G.T. Lonergan (Biotechnology Letters, 2004)

Phylogeny of Australasian venomous snakes (Colubroidea, Elapidae, Hydrophiinae) based on phenotypic and molecular evidence - John D. Scanlon; Michael S. Y. Lee (Zoologica Scripta, 2004)
Scanlon, John D. & Lee, Michael S. Y. (2004). Phylogeny of Australasian venomous snakes (Colubroidea, Elapidae, Hydrophiinae) based on phenotypic and molecular evidence. — Zoologica Scripta , 33 , 335–366. Phylogenetic relationships among Hydrophiinae (Australasian and marine elapid snakes) are inferred using 87 characters from external, skeletal, hemipenial and internal anatomy, ecology, and chromosomes as well as available sequences of two mitochondrial genes (cytochrome b and 16S rRNA). Parsimony analysis of the combined data retrieves many widely accepted clades; while observed bootstrap or branch (Bremer) support for these is often weak, most have never been corroborated previously by a rigorous numerical analysis. Sea kraits ( Laticauda ) and Solomon Islands elapids are basal to the remaining hydrophiines (Australian terrestrial forms and hydrophiin sea snakes). The latter clade includes three main lineages: a large‐bodied oviparous lineage, a small‐bodied oviparous lineage, and a viviparous lineage (which also includes the hydrophiin sea snakes, strongly reaffirmed as monophyletic). While the Solomons retain a relictual fauna, New Guinea has less endemism and has been invaded multiple times by Australian lineages, so there is no clear ‘stepping stone’ pattern supporting a northern (Asian, rather than Gondwanan) biogeographical origin.

Canopy scale measurements of CO 2 and water vapor exchange along a precipitation gradient in southern Africa - Todd M. Scanlon; John D. Albertson (Global Change Biology, 2004)
Short‐term measurements of carbon dioxide, water, and energy fluxes were collected at four locations along a mean annual precipitation gradient in southern Africa during the wet (growing) season with the purpose of determining how the observed vegetation–atmosphere exchange properties are functionally related to the long‐term climatic conditions. This research was conducted along the Kalahari Transect (KT), one in the global set of International Geosphere‐Biosphere Program transects, which covers a north–south aridity gradient, all on a homogenous sand formation. Eddy covariance instruments were deployed on a permanent tower in Mongu, Zambia (879 mm of rainfall per year), as well as on a portable tower in Maun (460 mm yr −1 ), Okwa River Crossing (407 mm yr −1 ), and Tshane (365 mm yr −1 ), Botswana for several days at each site. The relationships between CO 2 flux, F c , and photosynthetically active radiation were described well by a hyperbolic fit to the data at all locations except for Mongu, the wettest site. Here, there appeared to be an air temperature effect on F c . While daytime values of F c routinely approached or exceeded −20 μmol m −2 s −1 at Mongu, the magnitude of F c remained less than −10 μmol m −2 s −1 when the air temperature was above 27°C. Canopy resistances to water vapor transfer, r c , displayed an overall decline from the wetter sites to the more arid sites, but the differences in r c could be almost exclusively accounted for by the decrease in leaf area index (LAI) from north to south along the KT. Ecosystem water use efficiency (WUE), defined as the ratio of net carbon flux to evapotranspiration, showed a general decrease with increasing vapor pressure deficit, D , for all of the sites. The magnitudes of WUE at a given D , however, were dissimilar for the individual sites and were found to be stratified according to the position of the sites along the long‐term aridity gradient. For example, Mongu, which has the wettest climate, has a much lower WUE for like levels of D than Tshane, which historically has the most arid climate. Given the similar inferred stomatal resistances between the sites, the disparate carbon uptake behavior for the grass vs. woody vegetation is the likely cause for the observed differences in WUE along the aridity gradient. The short‐term flux measurements provide a framework for evaluating the vegetation's functional adaptation to the long‐term climate and provide information that may be useful for predicting the dynamic response of the vegetation to future climate change.

Surface Water Transport of Lead at a Shooting Range - J. R. Craig; J. D. Rimstidt; C. A. Bonnaffon; T. K. Collins; P. F. Scanlon (Bulletin of Environmental Contamination and Toxicology, 1999)

Pathotyping isolates of Newcastle disease virus using antipeptide antibodies to pathotype-specific regions of their fusion and hemagglutinin-neuraminidase proteins - D. B. Scanlon; G. L. Corino; B. J. Shiell; A. J. Della-Porta; R. J. Manvell; D. J. Alexander; A. N. Hodder; J. J. Gorman (Archives of Virology, 1999)